Adulticide efficacy of essential oil from Piper retrofractum vahl against Aedes aegypti and Culex quinquefasciatus - T. Subsuebwong (2018)
© 2016, Malaysian Society for Parasitology. All rights reserved. Essential oil was extracted from the fresh fruit of Piper retrofractum Vahl by water distillation method. The yield of extraction was estimated at 0.125%. Adulticidal activity was tested against 2-5 days-old non-blood-fed female Aedes aegypti and Culex quinquefasciatus by topical application. Six concentrations of essential oil dissolved in acetone were prepared in 5%, 7%, 9%, 11%, 13% and 15%. The solution (0.5 μL) was on the pronotum of mosquito, and mortality was observed after 24 hours of exposure. The LD50 and LD99 of essential oil in acetone against Ae. aegypti (8.86%, 23.21%) and Cx. quinquefasciatus (6.95% and 17.35%,) was measured. This is the first report of adulticidal activities of essential oil from P. retrofractum against mosquito vectors.